Prioritizing choice and assent in the assessment and treatment of food selectivity. (2nd January 2023) - Gover, Holly C.; Hanley, Gregory P.; Ruppel, Kelsey W.; Landa, Robin K.; Marcus, Juliana
Abstract : Food selectivity affects up to 72% and 45% of individuals with and without disabilities, respectively, and there is a need for interventions that rely on positive, unrestrictive strategies. We evaluated an assessment and treatment package for food selectivity for young children with developmental disabilities that prioritized caregiver collaboration, client autonomy, and did not rely on restrictive procedures (e.g. escape extinction). The process involved: (a) collaborating with caregivers on the selection of foods and design of the children's functional analyses; (b) indirectly and directly measuring food preferences prior to treatment; (c) evaluating the sensitivity of mealtime problem behavior to environmental variables through an interview-informed synthesized contingency analysis (IISCA); and (c) incorporating the assessment results into a progressive treatment process consisting of choice-making opportunities and differential reinforcement of successive approximations to consumption. Children also had the ability to opt in and out of treatment sessions. The treatment was effective in increasing consumption of nonpreferred foods and successfully extended to caregivers. Practical implications and directions for future research are discussed.